Pengaruh Iklan di Media TV dan Kesadaran Merek Terhadap Proses Keputusan Pembelian Body Lotion Citra - Kintani Mayastika Dewanti (FEB Universitas Sultan Ageng Tirtayasa, 2016)
The purpose of this research is to know the influence of advertising on TV medium and brand awareness towards buying decision process body lotion Citra (survey at female student of SMAN 1 Purwakarta). This research is using quantitative approach and processing method using path analysis with software SPSS ver.20. Data used primary data from 100 female student of SMAN 1 Purwakarta. This research shows that there is influence of advertising on TV medium and brand awareness towards buying decision process body lotion Citra at female student of SMAN 1 Purwakarta.